Influence of the transducer bandwidth on compressed ultrasonic echoes - Ihor TROTS; Andrzej NOWICKI (Archives of Acoustics)
The aim of this work is to explore and analyze the influence of the transducer bandwidth on the compressed echoes resulted from the Golay complementary codes transmission. For that reason, a computer simulation and experimental verification were performed that reflected the influence of the transducer bandwidth on the distortion of a signal. This study helps to elucidate why the echoes ringing is present for narrow bandwidth transducers. As known, the shape and symmetry of the pulse waveform and its interaction with the transducer bandwidth and its tuning circuitry have a profound effect on the pulse echo performance achievable from a medical scanning probe. The computer simulation was performed using the Matlab software for different fractional transducer bandwidths - from wideband transducers of 100% (ideal case), 90%, 75% to narrowband ones of 50% and 25%. The 16-bits Golay complementary sequences at nominal frequency of 1 MHz were used to illustrate the transducer bandwidth influence on the resulted signal. It was shown that the decreasing of the transducer bandwidth results in a considerable drop of the amplitude of the compressed echoes from 20.1 V for the 90% fractional bandwidth down to: 17.1 V, 12.5 V and 6.6 V for 75%, 50% and 25% bandwidths, respectively. The widths of the compressed echoes were widening at the same time from 708 ns up to 2.38 μs reducing the axial resolution from about 1 mm to over 3.6 mm. In the experiments, two transducers with different fractional bandwidths of 70% and 35% and nominal frequencies of 4.8 MHz and 6 MHz, respectively, were used.